POTENSI TANAMAN HERBAL SEBAGAI ANTIMIKROBIAL PADA IKAN LELE SANGKURIANG (Clarias sp.) - Nora Simatupang; Dwi Anggraini (Universitas Sriwijaya, 2013)
ABSTRACT Motile aeromonad septicaemia (MAS) is caused by the bacterium Aeromonas hydrophila. The use of plant (natural materials) from herbal plants such as garlic, lime, turmeric and mengkudu can be as an alternative way to inhibit the activity of A. hydrophila by their active substances which have potency as an antibacterial and immunostimulant. The aim of this study was to analyze the potential of using a mixture of herbal plants to control of A. hydrophila in catfish sangkuriang (Clarias sp.). There were split in two kind of doses namely, preventive garlic;lemon 0,625% and turmeric;mengkudu 1,5%. The preventive treatment was given for two weeks before challenging test. The curative treatment was performed on one week after challenging test. Challenging test was carried out by intramuscularly injecting of 0,1 mL A. hydrophila (105cfu/ml) into the fish. The results of in vitro at doses of 5% of each extract showed antimicrobial. In the in vivo test, extracts of garlic and lime showed antimicrobial at a doses of 0.625%, while turmeric and mengkudu extracts effective inhibited in a doses of 1,5%. Key word: Herbal plants, antimicrobial, catfish sangkuriangÂ